Critical Thinking Skills Reviewed from Communication Skills of the Primary School Students in STEM-Based Project-Based Learning Model (Journal of Primary Education, 2020)
Critical thinking skills are important to practice early on in elementary school. It is believed that STEM based education could trigger the students to more critical. Individuals who have critical thinking skills will be able to communicate well. Many research results show that critical thinking skills can be stimulated by applying project-based learning in class. This research aims to describe critical thinking skills based on communication skills by using STEM-based Project-Based Learning. The research is a mixed-methods study. The population of this research consisted of fifth graders of Public Primary School 3 Pakis. The research instruments used were critical thinking skills tests, communication skills questionnaires and interview guidelines. The quantitative data was selected by purposive sampling technique. The qualitative data was based on the communication skills levels: high, moderate, and low. Based on the triangulation data it shows that students with high critical thinking skills reached the aspect of analyzing arguments; the moderate level could achieved simple aspects of explanation; while the lower level critical thinker only reaches the aspect of focusing questions. The STEM approach applied in project-based learning is able to encourage students to be able to communicate verbally and improve their critical thinking skills in solving problems.